Guide selection using a CRISPRa system to activate parkin gene related to parkinson's disease (2023)
Parkinson's Disease (PD) is a neurodegenerative disorder that causes a loss in motor capabilities, tremors, bradykinesia, cognitive capacity, and sometimes dementia. The Parkin gene is an essential gene that has a fundamental role in the ubiquitination of proteins and the maintenance of mitochondria. Mutations in the Parkin gene are related to PD. In this study, we got the required DNA to activate the Parkin gene through a CRISPR activation system as a therapeutical objective. We show that using the DH5 alpha strain of E. coli is not the best option to transform and clone the plasmids that have the genetic information. The DH10B strain is a better option for obtaining linearized DNA. It strains requires fewer steps to achieve colonies with the plasmid, and the amount of DNA recovered is notably more significant than with the DH5 alpha.